2019
DOI: 10.1002/ajoc.201900296
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Sustainable Approach for Selective Halogenation of Anilides, Benzanilides, Sulphonamides and Heterocycles

Abstract: An efficient green and sustainable protocol has been devised for the selective oxidative halogenation of acetanilides, benzanilides, sulphonamides, and heterocyclic compounds, using easily available NaX as a halogen source and Oxone as a powerful oxidant. Reaction products were analyzed by GC-MS. Defined experimental conditions provided the mono and dihalo compounds. The present protocol is simple and environmentally benign to conduct the laboratory scale halogenations and can be extended to prepare industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…With the discovery and optimized conditions of in situ RBS generation from FeBr 2 –H 2 O 2 and CeBr 3 –H 2 O 2 , we set out to expand the scope of arene bromination ,, (Table -1). Brief examination of the substrate scope revealed that only electron-rich arenes were suitable for bromination to provide p -bromoarene products ( 2a – 2g ) in 52–97% yields ( p : o > 20:1) (Table -1).…”
Section: Resultsmentioning
confidence: 96%
“…With the discovery and optimized conditions of in situ RBS generation from FeBr 2 –H 2 O 2 and CeBr 3 –H 2 O 2 , we set out to expand the scope of arene bromination ,, (Table -1). Brief examination of the substrate scope revealed that only electron-rich arenes were suitable for bromination to provide p -bromoarene products ( 2a – 2g ) in 52–97% yields ( p : o > 20:1) (Table -1).…”
Section: Resultsmentioning
confidence: 96%
“…For the syntheses of 11u and 11w (each a pair of diastereomers), the R 5 substituent was also transformed from one entity to another, designated in Scheme as 6d (R 5 substituent) being transformed to 6b (R 5 ′ substituent). Only a few examples exist in the literature for the chlorination of triazole 5-position anions , and for the nucleophilic displacement of similarly positioned 5-chlorotriazoles. The intermediates 6a–d were converted to 11a–w by heating with barbituric acid under aqueous acid conditions, during which deprotection of the ketal occurred in situ, releasing the aldehyde for the T-reaction. Overall, the versatility of the sequences in Scheme permitted the selective substitution at either 3- or 5-position of the triazole.…”
Section: Resultsmentioning
confidence: 99%
“…Like other green oxidants such as O 2 and H 2 O 2 [ 5 ], peroxymonosulfate (PMS, Oxone ® ) has been widely used: (1) in the academia to develop new synthetic protocols [ 6 ]; (2) in pharmaceutical companies to promote oxidative stress testing of active pharmaceutical ingredients (API) to predict their degradation [ 7 ]; and (3) in hypersaline industrial wastewaters to remove organic contaminants [ 8 , 9 , 10 ]. This safe, sustainable, and inexpensive oxidant has shown extraordinary reactivity with alkaline metal halide salts [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and with hydrogen halides (HCl, HBr and HI) [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%